PENERAPAN KETERAMPILAN BERBAHASA INDONESIA BERBASIS PENDEKATAN EXPERIENCE BASED EDUCATION PEGAWAI DISHUB BATAM - Yunisa Oktavia; Emil Eka Putra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
Bahasa Indonesia has developed rapidly. Bahasa Indonesia has been taught in many countries and used in written or spoken context, formally and informally. As one of government departments, Batam’s Department of Transportation certainly has to take part in promoting the proper use of Bahasa Indonesia. Unfortunately, there are a lot of problems faced by the official of Batam’s Department of Transportation. The problems in written context can be seen in the letter, announcement, or other written information issued by this department. In spoken context, the problems can be seen in the context of politeness used by the official. These problems then are tried to be solved by the community service team through this community service program. This program is aimed at reducing the problems faced by the official in using Bahasa Indonesia. This program adopted Experience Based Education Approach which rely on knowledge and experience sharing. The result of this community service shows that this program has successfully become a means of self reflection and conceptualization of proper use of Bahasa Indonesia which further enable the participant to analyze the mistakes made in using Bahasa Indonesia. This result is then expected to be one of solutions to problems faced by the officials in using Bahasa Indonesia.